2018
DOI: 10.3750/aiep/02454
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth, and diet of axillary seabream, Pagellus acarne (Actinopterygii: Perciformes: Sparidae), in the central Aegean Sea

Abstract: Background. The knowledge of the age, growth, and feeding ecology of fish species is essential for conservation, monitoring, and management activities required for the sustainable use of fish stocks. The objective of this work was to describe the growth and feeding of Pagellus acarne from the Gulf of İzmir, central Aegean Sea. The information provided in this study contributes to the knowledge which is for sustainable management applications. Material and methods. The study was carried out to investigate the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…Both female and male Pagelus acarne exhibit positive allometric growth as previously reported for Mediterranean and Atlantic coast (Pajuelo and Lorenzo, 2000;Morey et al,, 2003;Coelho et al, 2005;Ceyhan et al,2009;Velasco et al, 2010;Soykan et al, 2015;İlhan 2018;Di Maio et al,2020). On the contrary in the Aegean Sea, Moutopoulos and Stergiou (2002) found that negative allometry for Pagellus acarne in the Aegean Sea.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Both female and male Pagelus acarne exhibit positive allometric growth as previously reported for Mediterranean and Atlantic coast (Pajuelo and Lorenzo, 2000;Morey et al,, 2003;Coelho et al, 2005;Ceyhan et al,2009;Velasco et al, 2010;Soykan et al, 2015;İlhan 2018;Di Maio et al,2020). On the contrary in the Aegean Sea, Moutopoulos and Stergiou (2002) found that negative allometry for Pagellus acarne in the Aegean Sea.…”
Section: Discussionsupporting
confidence: 66%
“…The biology of this species has been reported in different regions of the Aegean Sea (Tosunoğlu et al, 1997, Soykan et al, 2015, and in the Greek waters (Stergiou et al, 1997). Several authors studied age, growth and reproductive biology of axillary seabream in the Mediterranean and Atlantic (Phân and Kompowski 1972, Andaloro 1982, Campillo 1992, Arculeo et al, 2000, Dominguez 2000, Pajuelo and Lorenzo 2000, Zoubi 2001, Coelho et al, 2005, Abecasis et al, 2008, Velasco et al, 2011, İlhan et al, 2018, Keddar et al, 2020, Di Maio et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Araştırma materyalini oluşturan yabani mercan balığının biyolojisi ve büyümesi üzerine gerçekleştirilmiş çok sayıda çalışma (Coupe, 1952;Mater, 1976;Lê-Trong Phâń & Kompowski, 1972;Andaloro, 1982;Domanevskaya, 1982;Domanevskaya & Patokina, 1984;Santos vd., 1995;Özaydın, 1997;Tosunoğlu vd., 1997;Pajuelo & Lorenzo, 2000;Coelho vd., 2005;Velasco vd., 2011;Soykan vd., 2015Soykan vd., Öztekin vd. 2015İlhan, 2018;İnnal & Katselis, 2019;Yedier vd., 2019) ile türün üreme özellikleri ile ilgili çalışmalar da mevcuttur (Stergio vd., 1997;Pajuelo & Lorenzo, 2000;Zoubi, 2001;Velasco vd., 2011;Bensahla Talet vd., 2013;Despoti & Stergiou, 2013;Boufersaoui & Harchouche, 2015;Dragičević vd., 2015;Bensahla Talet vd., 2017ve Bentata-Keddar vd., 2020.…”
Section: Introductionunclassified
“…Further, there is no published information yet regarding comparative evaluation of amino acid pattern in farmed or wild axillary seabream, considered as a new candidate species for the Mediterranean aquaculture industry. The oceanodromous axillary seabream is a benthopelagic fish species living in various types of sea bottoms, especially seagrass beds, from sandy areas down to 500 m depth, usually 40–100 m environment, the young individuals remain in shallow waters close to the shore (Bauchot, & Hureau, ), and is reported to prey on a wide variety of small organisms, mainly copepoda (harpacticoida), polychaeta, and decapoda with seasonal variations in adult diets, and can be considered as a carnivorous, euryphagous and zooplanktivorous species (Fehri‐Bedoui, Mokrani, & Ben Hassine, ; Ilhan, ). The differences between farmed and wild fish with respect to their quality characteristics are a remarkable key factor to reveal and ensure that the aquaculture product meets regulatory nutritional requirements for human health and also consumer preferences when introducing new species for the fish farming sector.…”
Section: Introductionmentioning
confidence: 99%